Memahami Budaya Kaum Muda Sebuah Misiologi Baru di Jagad Maya - Darmanto D (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
The young generation is a very dynamic and unique, especially at the present time in which young people are connected to each other in ways that are unprecedented in previous generations. Advances in technology, particularly the internet and social media, changing times, increases creativity, patterns and relationships in the midst of a growing youth, encourage the creation of a culture of young people with different cultural communities that common. The Church will be missed and lost opportunities if it can't recognize and understand youth culture; so the Church needs to be entered in the community of young people so that young people can serve contextually, according to the truth of God's Word and right on target, so that young people have a spirituality which is good.